Some unpleasant properties of log-linearized solutions when the nominal rate is zero - R. Anton Braun; Lena Mareen Körber; Yuichiro Waki (Federal Reserve Bank of Atlanta, 2012)
Does fiscal policy have qualitatively different effects on the economy in a liquidity trap? We analyze a nonlinear stochastic New Keynesian model and compare the true and loglinearized equilibria. Using the loglinearized equilibrium conditions, the answer to the above question is yes. However, for the true nonlinear model, the answer is no. For a broad range of empirically relevant parameterizations, labor falls in response to a tax cut in the loglinearized economy but rises in the true economy. While the government purchase multiplier is above two in the loglinearized economy it is about one in the true economy.
Keywords: H30; E12; E62; E50; 330; monetary policy; fiscal policy; zero bound